The Determinan Niat Crowdfunders Dalam Menggunakan Model Wakaf Crowdfunding: Integrasi 3 Model dengan Kepercayaan Sebagai Mediasi - Siska Arie Novita; Rusgianto, Sulistya (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The potential of waqf is huge in Indonesia, but it has yet to be optimized. One of the developing waqf models is cash waqf. With the development of technology, it can be an opportunity to maximize the collection of cash waqf funds in Indonesia. This research aims to provide knowledge for waqf institutions to adopt financial technology in developing cash waqf as productive and social waqf. The research assesses the Technology Acceptance Model (TAM 3), Theory of Planned Behavior (TPB), Unified Theory of Acceptence and Use of Technology (UTAUT 2), Perceived Trust (PT) as a mediating variable in seeing the behavior of the muwakif. This study uses a structural equation modeling (SEM) analysis model to test the hypothesis. Based on puroisve sampling, distributing questionnaires through online surveys using google form from various regions. The respondents collected from this study were 126 from the questionnaires that had been given. The results showed that TAM3, TPB and UTAUT2 had no effect on crowdfunders' behavioral intentions. PT has a significant positive effect on behavioral intentions. UTAUT2 has an effect on behavioral intention mediated by PT. The results of this study provide advice to the waqf authority to increase waqf collection by integrating fintech and promoting to the entire community.